2020
DOI: 10.1039/c9cs00543a
|View full text |Cite
|
Sign up to set email alerts
|

Design and applications of metal-based molecular receptors and probes for inorganic phosphate

Abstract: We discuss and review the strategies of metal-based receptors targeting phosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 103 publications
0
48
0
Order By: Relevance
“…Hirashima et al and Honda and Saito suggested that the type of excipients or impurities in products can affect the frequency of precipitate formation during hemodialysis. 10,13) Interestingly, a precipitate in serum was observed only under conditions of higher serum concentrations of NFM (1 mg/mL) and citrate (2 mM) (Fig. 5).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Hirashima et al and Honda and Saito suggested that the type of excipients or impurities in products can affect the frequency of precipitate formation during hemodialysis. 10,13) Interestingly, a precipitate in serum was observed only under conditions of higher serum concentrations of NFM (1 mg/mL) and citrate (2 mM) (Fig. 5).…”
Section: Discussionmentioning
confidence: 91%
“…In some pharmaceutical products that contain NFM, citric acid or succinic acid are sometimes included to control the pH of the prepared solution. 10) Such additives may become anionic electrolytes and exchange with the mesilate of NFM. Hirashima et al and Honda and Saito suggested that the type of excipients or impurities in products can affect the frequency of precipitate formation during hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations